Climate Change and Plant Diseases: How Emerging Conditions Reshape Plant-Pathogen Interactions / Review Article - Rasha Saad Nuaman; Maeson N F abdula; Reyam Naji Ajmi (Peerian Journals Publishing, 2025)
Fluctuations in climate in the past few decades have had a dramatic effect on the relationship between plants and the pathogens that infect them at both the environmental and molecular levels. Global warming impacts a plant's defense system negatively by decreasing the immune chemicals manufactured within the plant, making it vulnerable to attack by disease. High humidity also affects the power of plants to close the spiracles in their leaves. The spiracles normally close to limit pathogen invasion, but under higher humidities, plants cannot effectively control these spiracles, and pathogenic fungi and bacteria are easier to enter through them. Increased atmospheric concentrations of carbon dioxide leads to changes in leaf morphology, for instance, through a reduction in spiracle density. This affects the ability of plants to resist specific pathogens. In the meantime, others such as powdery mildew take advantage of such changes to progress more rapidly. Climate change has caused some plant diseases to spread to new areas not originally infected by them, threatening agricultural production in these areas. Friendly microbes that live on plant roots and leaves are also pivotal in helping plants adjust to these climatic shifts and protect themselves from diseases. These microbes boost the immune power of plants and improve their resistance to drought and heat stress. In the future, the tendency is to use cutting-edge technologies such as genetic modification to enhance plant immunity, using artificial intelligence to predict disease outbreaks, and designing smart agricultural systems that provide farmers with early warnings and reduce reliance on chemical pesticides, making agriculture sustainable during climate change
Keywords: Climate Change; Plant Immunity; Pathogen Interaction